Digesting the Indigestible: Microplastic Extraction From Prawn Digestive Tracts - Li, Joan Y. Q.; Nankervis, Leo; Dawson, Amanda L. (Frontiers in Environmental Chemistry, 2022)
Microplastics (MPs) have become ubiquitous in the marine environment, and are likely ingested by a broad cross-section of marine life. The extent to which marine organisms ingest MPs is uncertain due to limitations in analytical methods. Effective identification and analysis of ingested MPs is a precursor to understanding their impact on marine organisms and their human consumers. This is particularly challenging for crustaceans, due to the chitin present in their exoskeleton and digestive systems, which is resistant to chemical degradation. This study presents a novel method that can efficiently break down the stable organic tissue of banana prawns (Penaeus merguiensis), and subsequently isolate putative MP polymers from within the digestive tract without damaging their integrity. Five treatments were examined for their capacity to break down chitin from the prawn digestive system; namely acid, alkaline, oxidant, enzyme and microwave assisted oxidant digestion. Gravimetric and image analysis revealed that the organic tissue of the prawn gastrointestinal tract can be effectively removed by acid, oxidant, and microwave assisted oxidant digestion methods. However, testing on seven reference polymers (polyamide (PA), polyethylene (PE), polyester (PES), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), and rayon) revealed significant degradation when exposed to acid digestion. Overall, microwave assisted oxidant digestion achieved the best recovery rate of spiked MPs (>90%) with minimal size, shape, and Fourier transform infrared (FTIR) spectral changes for all polymers except for rayon. These results highlight a new direction for tissue removal and MP extraction in crustacean ingestion studies.